The effects of LiTi2(PO4)3 modification on the performance of spherical Li1.5Ni0.25Mn0.75O2+δ cathode material. Issue 52 (11th May 2016) - Wang, Gang; Wang, Xianyou; Yi, Liling; Wang, Lianwu; Yu, Ruizhi; Liu, Meihong; Wang, Di; Ren, Qifang; Yang, Xiukang
Abstract : Effect of LiTi2 (PO4 )3 coating on the electrochemical properties of spherical layered Li1.5 Ni0.25 Mn0.75 O2+ δ cathode material. Abstract : The spherical layered Li1.5 Ni0.25 Mn0.75 O2+ δ cathode material is successfully modified with a LiTi2 (PO4 )3 (LTP) coating through a facile hydrothermal route. The effects of LTP modification on the structure, morphology and electrochemical performance of Li1.5 Ni0.25 Mn0.75 O2+ δ cathode material are investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), transmission electron microscopy (TEM) and charge–discharge tests. The results reveal that, among all the as-prepared samples, the sample modified with 3 wt% LTP delivers the highest reversible capacity of 254.9 mA h g −1 at 0.1C and excellent capacity retention of 95.8% after 100 cycles at 0.5C in a voltage range of 2–4.6 V. Additionally, the lithium-rich cathode material modified by LTP also exhibits superior rate capability with a capacity of 103.2 mA h g −1 even at a high discharge rate of 10C. The enhanced rate capability and cycling performances are attributed to the surface protective layer of LTP, which not only protects the surface of the active materials from electrolyte corrosion but also reduces the charge transfer resistance. Therefore, the modification with LTP of spherical lithium-rich cathode materials will be a promising technical route for the preparation of high performance lithium-ion battery cathode materials.